USE OF MENTAL MAP IN FORMATION OF CLINICAL THINKING OF STUDENTS (Intent Research Scientific Journal, 2025)
This article is devoted to the role and importance of mental maps in the development of clinical thinking of students. Clinical reasoning is a complex cognitive process that includes critical skills such as diagnosis, differential diagnosis, treatment strategy development, and decision making. Mental maps can be an effective tool in shaping students' clinical thinking by organizing information, identifying problems, and making connections between them. The article analyzes the theoretical basis of mental maps, the methods and advantages of their use in clinical education, as well as the existing limitations.